Wasan the fascination of traditional Japanese mathematics - Sakurai, Susumu; Ford, Emma; Sekimori, Gaynor (Tokyo Japan Publishing Industry Foundation for Culture, 2018)
Wasan - a unique form of Japanese mathematics - was developed during the Edo period (1603-1868), a time when the entire country was isolated from the rest of the world. Mathematics was enjoyed as a form of entertainment by adults and children alike and by people of all social classes. Jink?oki, an extraordinary mathematics textbook, was used at private elementary schools called terakoya and became a bestseller that could be found in every household. Furthermore, world-class works were produced by Japanese mathematicians such as Seki Takakazu and Takebe Katahiro. This book explores the beauty and fascination surrounding wasan by providing a guided tour that goes back in time over three hundred years and navigates through the mysterious and incredible world of mathematical wizardry found during the Edo period in Japan.
"This book is a translation of 'Muchu ni naru! Edo no sugaku' (Shueisha Inc., 2012) which was originally published under the title 'Edo no s?ugaku ky?okasho' by Shueisha International Inc. in 2009"--title page verso. - Impressum auch in Japanich.
Keywords: Mathematics, Japanese